Talking down the competitors: How do investment banking relationships influence analysts' forecasts? - Si, Fangbo; Yu, Xiaoxu; Zhang, Huai (Contemporary Accounting Research, 2025)
Abstract Our study reveals that financial analysts issue more pessimistic forecasts for their investment banking clients' competitors than for unrelated firms. Our evidence is consistent with this behavior stemming from analysts' strategic incentives rather than their true beliefs. We find that analysts' pessimism for the client's competitors is more pronounced when the client is more important to analysts' brokerage houses, when high uncertainty prevents competitors from detecting analysts' strategic motives, and when analysts' brokerage houses are less prestigious. Additionally, we explore the economic consequences of the pessimism from the perspectives of the covered firms, brokerage houses, and financial analysts. Finally, we consider the impact of the 2003 Global Analyst Research Settlement. Overall, our results demonstrate that issuing pessimistic forecasts for clients' competitors is an understudied channel through which analysts curry favor with their investment banking clients.